ALTMAN Z”-SCORE MODIFIKASI SEBAGAI ALAT PREDIKSI KEBANGKRUTAN PADA PERUSAHAAN TRANSPORTASI DI ERA PANDEMI COVID 19 - Yulianti, Sinta Dwi; Linawati, Linawati; Sugeng, Sugeng (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The transportation sector is a sector that has a crucial position in the national economy. Therefore, maintaining and improving the company's financial health needs to be done in order to avoid bankruptcy. This study aims to analyze bankruptcy predictions using the Altman Z”-Score method for transportation companies listed on the Indonesia Stock Exchange in 2019-2021. The research approach used is descriptive quantitative. The research subjects were 15 transportation companies that were listed and audited on the IDX with the presentation of Rupiah in their financial statements. The results showed that in 2019 there were 7 transportation companies classified as bankrupt, 4 companies classified as prone to bankruptcy and 4 companies classified as healthy. Then in 2020 there were 10 companies classified as bankrupt, 2 companies classified as prone to bankruptcy, and 3 companies classified as healthy. Furthermore, in 2021 there are 6 companies classified as bankrupt, 4 companies classified as vulnerable, and 5 companies classified as healthy. Based on the results of the Z”-Score during 2019-2021 there was a trend of fluctuating financial conditions.